INFORMATION THREATS IN THE MODERN WORLD - Khumoyun, Abduvasitov (MMIT Proceedings, 2023)
In the process of globalization, we live in an information age when, as a result of the rapid development of computer technology, the flow of information is increasingly accelerating, exerting its influence on the thinking of all people on earth. Information is the whole set of information about the world around us, about all kinds of processes occurring in it that can be perceived by living organisms, electronic machines and other information systems. This is how we perceive the concept of “information” in the modern world. This article is devoted to the problem of threats in the information flow.